2007 IEEE/ASME International Conference on Advanced Intelligent Mechatronics 2007
DOI: 10.1109/aim.2007.4412524
|View full text |Cite
|
Sign up to set email alerts
|

How self-locking reduces actuators torque in climbing snake robots

Abstract: Minimization of actuators torque in snake robots reduces the energy consumption and shrinks the robot dimensions. In this paper a mathematical model for climbing concertina movement is developed. The formulation is then used to show how torque is optimized in concertina movement. The results show that the optimum occurs when self-locking takes place. Self-locking implies zero actuator torque at each joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The robot was able to perform locomotion in different pipes and elbows. In [8], Barazandeh proposed a mathematical model of a climbing snake robot using a concertina pattern. By optimizing the proposed model, the results showed that self-locking could occur during the course of climbing, resulting in zero actuator torque.…”
Section: Review Of Snake Robot Applications In a Pipementioning
confidence: 99%
See 1 more Smart Citation
“…The robot was able to perform locomotion in different pipes and elbows. In [8], Barazandeh proposed a mathematical model of a climbing snake robot using a concertina pattern. By optimizing the proposed model, the results showed that self-locking could occur during the course of climbing, resulting in zero actuator torque.…”
Section: Review Of Snake Robot Applications In a Pipementioning
confidence: 99%
“…This model describes surfaces with the presence of liquid or solid oil. Stribeck friction can be expressed by Equation 8: (8) where is sliding speed, is Stribeck velocity, and k is an exponent. All mentioned friction models are shown in Figure 15.…”
Section: Friction Modelsmentioning
confidence: 99%
“…Chirikjian and Burdick implemented linear progression on their planar snake robot and Yim also implemented linear progression on his modular polybots [22]. Other research into robotic snake gaits includes Chirikjian and Burdick's basic research on sidewinding [4], and Barazandeh et al's examination of concertina locomotion [23]. Gonzalez-Gomez et al have demonstrated a model for various gaits that is perhaps the most similar to that presented here; however, their model is based on a set of coupled functions individually describing the angle for each joint, rather than a single function for the entire mechanism [24,25].…”
Section: Prior Snake Robot Modelingmentioning
confidence: 99%
“…[1][2][3] However, a relatively small number of studies on snake-like climbing robots, which can be divided into inner-climbing and outer-climbing types, have been conducted. [4][5][6] The outer-climbing type, as the current focus of research, is operating on the outer wall of cylinder tube to fulfill the climbing motion by winding. Nonetheless, the multiple degrees of freedom of snake-like robots would render the difficulty in inverse kinematic solution.…”
Section: Introductionmentioning
confidence: 99%